2013
DOI: 10.1158/0008-5472.can-13-1355
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Stem Cells Are Regulated by Interleukin-8 Signaling in a Tumoral Perivascular Niche

Abstract: Glioblastoma multiforme (GBM) contains a subpopulation of cancer stem-like cells (CSCs) believed to underlie tumorigenesis and therapeutic resistance. Recent studies have localized CSCs in this disease adjacent to endothelial cells (ECs) in what has been termed a perivascular niche, spurring investigation into the role of EC-CSC interactions in GBM pathobiology. However, these studies have been limited by a lack of in vitro models of three-dimensional disease that can recapitulate the relevant conditions of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
152
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(159 citation statements)
references
References 49 publications
5
152
0
2
Order By: Relevance
“…Extensive work in solid tumors has shown that IL8 is critical in survival, invasion, and proliferation of cancer cells [21][22][23][24] and might be an important regulator of cancer stem cell activity. [25][26][27] Activation of multiple pathways by IL8, including phosphatidylinositol 3-kinase/protein kinase B (AKT), phospholipase C/protein kinase C, and mitogen-activated protein kinase (MAPK) signaling, leads to increased expression of various The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work in solid tumors has shown that IL8 is critical in survival, invasion, and proliferation of cancer cells [21][22][23][24] and might be an important regulator of cancer stem cell activity. [25][26][27] Activation of multiple pathways by IL8, including phosphatidylinositol 3-kinase/protein kinase B (AKT), phospholipase C/protein kinase C, and mitogen-activated protein kinase (MAPK) signaling, leads to increased expression of various The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IL8 could be a multifaceted inflammatory mediator used by the tumor to simultaneously promote angiogenesis (1,(3)(4)(5)(6)(7)(8)(9), co-opt immunosuppressive populations (1,(3)(4)(5)(6)(7)(8)(9), and disrupt the routes of migration of professional antigen-presenting dendritic cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…IL8 does not only attract neutrophils but also monocytes to inflamed tissues (2). Tumor cells constitutively produce IL8 (2)(3)(4)(5)(6)(7)(8)(9) and hence plasma concentrations of IL8 reflect tumor burden (2) and determine prognosis (2)(3)(4)(5)(6)(7)(8)(9). IL8 is functional on CXCR1 and CXCR2 where it induces chemotactic responses.…”
Section: Introductionmentioning
confidence: 99%
“…GBM cells, which secrete IL-8, promote angiogenesis and microvascular endothelial permeability [9]. IL-8 can also regulate GBM associated Bcancer stem cells( CSCs) and was associated with tumor grade in astrocytic neoplasms [31]. IL-8 induces the growth and migration of CSCs via receptors CXCR1 and CXCR2.…”
Section: Discussionmentioning
confidence: 99%